Exercise, brain plasticity, and depression - Zhao, Jin‐Lei; Jiang, Wan‐Ting; Wang, Xing; Cai, Zhi‐Dong; Liu, Zu‐Hong; Liu, Guo‐Rong (CNS neuroscience & therapeutics, 2020)
Depression is a common mental disorder characterized by high incidence, high disability, and high fatality, causing great burden to the society, families, and individuals. The changes in brain plasticity may be a main reason for depression. Recent studies have shown that exercise plays a positive role in depression, but systematic and comprehensive studies are lacking on brain plasticity changes in depression. To further understand the antidepressive effect of exercise and the changes in brain plasticity, we retrieved related literatures using key words “depression,” “depressive disorder,” “exercise,” “brain plasticity,” “brain structure,” and “brain function” from the database of Web of Science, PubMed, EBSCO host, and CNKI, hoping to provide evidence for exercise in preventing and treating depression. Increase in exercise has been found negatively correlated with the risk of depression. Randomized controlled experiments have shown that aerobic exercise, resistance exercise, and mind‐body exercise can improve depressive symptoms and levels. The intensity and long‐term effect of exercise are now topical research issues. Exercise has been proven to reshape the brain structure of depression patients, activate the function of related brain areas, promote behavioral adaptation changes, and maintain the integrity of hippocampal and white matter volume, thus improving the brain neuroprocessing and delaying cognitive degradation in depression patients. Future studies are urgently needed to establish accurate exercise prescriptions for improving depressive symptoms, and studies on different depressive populations and studies using multimodal brain imaging combined with multiple analytical methods are also needed.